2020
DOI: 10.36085/jkmu.v8i2.1059
|View full text |Cite
|
Sign up to set email alerts
|

Adaptasi Perilaku Caring Perawat pada Pasien Covid-19 di Ruang Isolasi

Abstract: Caring is a nursing action based on the desire to understand, help and reduce suffering by taking the best actions for health. Caring behavior must also be given to Covid-19 patients. The research objective was to determine the adaptation of nurses' caring behavior in Covid-19 patients in the RSUD Dr. Isolation room. M. Yunus Bengkulu. This research is a descriptive study with a qualitative approach, involving 10 participants as research subjects. Data collection was carried out through in-depth interviews and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 0 publications
0
8
0
11
Order By: Relevance
“…This assumption is supported by Yustisia et al (2020), caring must be shown by nurses in every job they do, when they talk, greet, provide health education, counseling and listen to clients. Courtesy is caring behavior of nurses in respecting human dignity, namely clients and their families, instilling mutual trust, respecting humanity by being friendly to clients.…”
Section: Diagram 1 Distribution Of Respondents Based On Caring Behavi...mentioning
confidence: 99%
“…This assumption is supported by Yustisia et al (2020), caring must be shown by nurses in every job they do, when they talk, greet, provide health education, counseling and listen to clients. Courtesy is caring behavior of nurses in respecting human dignity, namely clients and their families, instilling mutual trust, respecting humanity by being friendly to clients.…”
Section: Diagram 1 Distribution Of Respondents Based On Caring Behavi...mentioning
confidence: 99%
“…Total kasus konfirmasi gobal per tanggal 11 Februari 2021 adalah 106,991,090 kasus dengan CFR 2,2% [3]. Covid-19 tidak hanya berdampak pada masyarakat umum, tetapi juga tenaga kesehatan pemberi layanan klinis [4]. Berdasarkan data Tim Mitigasi PB IDI bahwa tingkat kematian tenaga Kesehatan di Indonesia merupakan tertinggi di Asia, dan tiga besar seluruh Faqih Ruhyanudin / Nurses' Experiences Confirmed Positive Covid-19: Qualitative Study dunia.…”
Section: Pendahuluanunclassified
“…This study reached saturation in the sixth participant-data analysis with Colaizzi Measures. The study identified six themes: 1) Lack of courage to report symptoms and carry out examinations, 2) Exposure to COVID-19 at their work, 3) Mild symptoms of Covid- 19,4) The most severe problem it felt was the psychological, 5) Efforts to heal with medication, 6) Support from workplace institutions and colleagues, 7) Religious, spiritual efforts, and 8) The sequelae after being healed. The negative stigma in the community towards covid survivors causes them to hide their illness so that the hospital and the surrounding community don't know about it.…”
mentioning
confidence: 99%
“…Dampak situasi pandemi saat ini benar-benar dirasakan oleh seluruh lapisan masyarakat, begitu juga dengan tenaga kesehatan. Mereka yang berada di garda terdepan tidak bisa ikut berkumpul dengan keluarga dalam menerapkan kebijakan "di rumah saja", sikap profesionalisme para tenaga kesehatan sangat diperlukan dalam hal ini [5]. Perawat sebagai salah satu tenaga kesehatan yang setiap harinya harus melakukan kontak langsung dan berperan sebagai caregiver bagi pasien positif covid-19, terutama pada perawat yang bekerja di Rumah Sakit rujukan untuk pasien covid-19 seperti Rumah Sakit milik Pmerintah memiliki resiko yang sangat tinggi dan cukup rentan dalam segi fisik maupun psikis, tercatat setidaknya sudah 12 orang perawat terinfeksi dan meninggal dunia akibat virus covid-19 [5].…”
Section: Pendahuluanunclassified
“…Mereka yang berada di garda terdepan tidak bisa ikut berkumpul dengan keluarga dalam menerapkan kebijakan "di rumah saja", sikap profesionalisme para tenaga kesehatan sangat diperlukan dalam hal ini [5]. Perawat sebagai salah satu tenaga kesehatan yang setiap harinya harus melakukan kontak langsung dan berperan sebagai caregiver bagi pasien positif covid-19, terutama pada perawat yang bekerja di Rumah Sakit rujukan untuk pasien covid-19 seperti Rumah Sakit milik Pmerintah memiliki resiko yang sangat tinggi dan cukup rentan dalam segi fisik maupun psikis, tercatat setidaknya sudah 12 orang perawat terinfeksi dan meninggal dunia akibat virus covid-19 [5]. Jumlah kasus yang dicurigai, terkonfirmasi, beban kerja berlebih, alat pelindung diri (APD) yang semakin berkurang jumlahnya, dan banyaknya pemberitaan-pemberitaan lewat media, serta kurangnya support lingkungan terhadap pekerjaan dan tanggung jawabnya bisa saja menjadi faktor munculnya beban mental pada tenaga kesehatan [6].…”
Section: Pendahuluanunclassified